Government Sector Fraud Analysis From the Fraud Diamond Perspective (Case Study of the Regional Financial Statements of the Southwest Papua Local Government) - Gunawan, Belinda; Nariman, Augustpaosa (SENTRALISASI, 2025)
Supreme Audit Board of Republic of Indonesia gave Adverse Opinion for the Financial Statement of Southwest Papua Local Government for the Fiscal Year 2023. Even the Audit Report of the Supreme Audit Board of The Republic of Indonesia on Financial Statement of Southwest Papua Local Government for the Fiscal Year 2023 does not mention "fraud" term on the report, it does not mean that Financial Statement of Southwest Papua Local Government for the Fiscal Year 2023 is fraud free. The purporse of this research is to provide a more explicit understanding to identify fraud indications in the Financial Statement of Southwest Papua Local Government for the Fiscal Year 2023, and to identify wheter the elements of fraud in expenditure audit findings are present or not, through analyisis using fraud theory.  This research relies on secondary data as its source and uses qualitative approach and case study methods. The scope of this study was limited by using the Audit Report of the Supreme Audit Board of The Republic of Indonesia on Financial Statement of Southwest Papua Local Government for the Fiscal Year 2023. The result of the study indicates that from 14 regional expenditure findings, there are indications of fraud in 12 expenditure findings based on analysis using component of fraud action theory and fraud diamond theory due to the fulfillment of the fraud elements.